The impact of fast-food video advertisements through the eyes of young creative industry practitioners - Woon, Pei Ying (Penerbit Universiti Kebangsaan Malaysia, 2024)
Video advertising has become a crucial marketing strategy for fast-food restaurants. While previous studies have identified factors influencing video advertisement effectiveness, these factors have yet to be investigated in light of current market preferences. In bridging this gap, it is crucial to consider the perspectives of young industry creative practitioners, who, with their dual roles as professionals and members of the target market, offer fresh insights into the factors influencing video advertisement effectiveness in alignment. Therefore, this study was conducted to investigate the fast-food video advertisements effectiveness in today’s market, specifically through the eyes of young creative industry practitioners. This study examines the effectiveness of fast-food video advertisements, focusing on content engagement, emotional arousal, information trustworthiness, and visual characteristics. Informant interview was utilized in the study, with data saturation achieved after collected insights from six interviewees who fulfilled the sampling criteria. The collected data underwent analysis using NVivo, involving coding and thematic analysis. The findings have substantiated strong relationships between visual attractiveness, content engagement, and the fast-food video advertisements effectiveness. However, it was determined that emotional arousal and information trustworthiness do not have a significant relationship with the fast-food advertisements effectiveness. Overall, this study contributes valuable insights for advertising agencies and offers a theoretical enhancement to existing models.